Motivation-Based Segmentation of Theme Park Visitors - Musfha, Syahla Karima; Setiyorini, Heri Puspito Diyah; Khaerani, Rijal (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Theme parks serve as significant tourism attractions that necessitate strategic reorientation, given the evolving expectations and experiences of tourists. The diverse motivation segments of theme park visitors indicate varying incentives, which impact their decisions and actions while at the theme park. This study aims to segment theme park visitors based on their visitation motivations, utilizing four primary variables: Challenge, Curiosity and need for different, Escape and relaxation, and Socializing with family and friends. A quantitative method was employed, collecting data through structured questionnaires from 450 respondents who had visited a theme park. Data were reduced using Principal Component Analysis (PCA) and K-Means to form clusters. The research findings indicate several motivations influencing theme park visitation, namely: Experiential Enjoyment Seekers, Escape and Fun-Oriented Visitors and Relationship-Driven Companions. This study contributes to expanding the existing literature on visitor motivations and offers managerial implications for theme park managers to adjust their marketing strategies according to these clusters, thereby enhancing visitor satisfaction and loyalty towards the theme park.